Permodelan ekonometrika dengan EViews 9 pada civitas akademik Universitas Muhammadiyah Makassar - Abd. Rahim; Diah Retno Dwi Hastuti (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
This activity is expected to help the students understand the processing techniques in inserting econometric data with EViews 9 program and can make decisions in analyzing the results as well as present them in discussion of their research. The identified problem is that the students of Agribusiness study program in Faculty of Agriculture of Universitas Muhammadiyah Makassar difficult in inserting the data into the program and interpreting the output data relating to econometric analysis both time-series data and cross-section data after processed using EViews 9 with econometric analysis on multiple regression approach. The result of this training shows that the students were enthusiast in attending the training because they never received such the training. Among forty participants joining this training, thirty-five of them are students and the other five are lecturers. Only twenty-five participants capable in processing and interpreting the output of econometric analysis data with the EViews 9 program. Expectedly, after joining the training the participants understand the processing technique in inputting econometric analysis data for EViews 9 program.